Survey of animal bite injuries and their management for an estimate of human rabies deaths in N'Djaména, Chad. Issue 12 (9th October 2013) - Frey, J.; Mindekem, R.; Kessely, H.; Doumagoum Moto, D.; Naïssengar, S.; Zinsstag, J.; Schelling, E.
Abstract Objective To estimate the annual human rabies incidence as a baseline prior to mass dog vaccination campaigns in N'Djaména, Chad. Methods Survey of animal bites, involving 50% of all healthcare providers in N'Djaména, from September 2008 to April 2009. Of 86 people exposed to a suspected rabid animal, 50% received post‐exposure vaccination and a further 8% had their wound cleaned. We estimated annual incidence of bites from suspected rabid animals of 12.9/100 000 and an incidence of 0.7 human rabies deaths/100 000, resulting in 7 estimated deaths (95% confidence interval 4–10 deaths) per year in N'Djaména. 14% of bite victims sought help from veterinarians. Conclusions Closer cooperation between physicians and veterinarians warrants more effective rabies control. The high proportion (42%) of potentially exposed people without post‐exposure vaccination or wound treatment necessitates urgent attention.